PENYULUHAN PADA WIRAUSAHA MUDA DALAM MEWUJUDKAN USAHA BERBASIS DIGITAL DI DESA TAJUR KECAMATAN CITEUREUP KABUPATEN BOGOR - Hasanudin Hasanudin; Dipa Teruna Awaloedin (Jurnal Abdimas Bina Bangsa, 2024)
This community engagement program aims to provide guidance on the role of young entrepreneurs in developing digital-based businesses in Tajur Village, Citeureup District, Bogor Regency. The team of lecturers aims to impart knowledge and motivation to young individuals and budding entrepreneurs concerning digital business, as well as principles of business and management. By facilitating relevant materials and modules, it is anticipated that participants will comprehend the significance of digital business within the context of the Covid-19 pandemic era. The outreach is directed towards boosting the enthusiasm and readiness of young individuals in running businesses, with the hope of fostering the growth of resilient entrepreneurship in the Bogor Regency and its surrounding areas. Through an understanding of digital business, participants are expected to confront challenges arising from the pandemic situation and broaden their insights regarding technological utilization in business. It is hoped that this outreach program will provide participants with knowledge and inspiration, thereby preparing them qualitatively and quantitatively to enter the world of entrepreneurship, making a positive impact on the economic growth in their respective regions. This research involves collaboration between the team of lecturers and the participants, with the expectation of generating a positive impact in increasing the number of competent and competitive young entrepreneurs in the current digital era